2018
DOI: 10.1093/alcalc/agy039
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Screening and Brief Intervention in Police Custody Suites: Pilot Cluster Randomised Controlled Trial (AcCePT)

Abstract: We achieved target recruitment and high brief intervention delivery if this occurred immediately after screening. Low rates of return for counselling and retention at follow-up were challenges for a definitive trial. Conversely, high consent rates for access to police data suggested at least some outcomes could be measured remotely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Whilst it is evident that the custody suite is a complex and busy environment (Wooff & Skinns, 2017), the findings of the linked feasibility trial demonstrate that arrestees rarely attend alcohol interventions that are offered on a subsequent occasion. This suggests that for intervention to occur, it must be provided opportunistically whilst the arrestee is in the custody suite (Addison et al, 2018). This has been found in other studies of alcohol intervention within primary care (Kaner et al, 2013), emergency care and elsewhere in the criminal justice system (Newbury-Birch et al, 2014).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Whilst it is evident that the custody suite is a complex and busy environment (Wooff & Skinns, 2017), the findings of the linked feasibility trial demonstrate that arrestees rarely attend alcohol interventions that are offered on a subsequent occasion. This suggests that for intervention to occur, it must be provided opportunistically whilst the arrestee is in the custody suite (Addison et al, 2018). This has been found in other studies of alcohol intervention within primary care (Kaner et al, 2013), emergency care and elsewhere in the criminal justice system (Newbury-Birch et al, 2014).…”
Section: Discussionmentioning
confidence: 83%
“…There is no standardised training required for this role, although AIRS workers typically have health and social care experience and/or qualifications. Further details of the trial are reported in the published protocol and within a linked paper reporting upon the findings of the feasibility trial (Addison et al, 2018).…”
Section: Samplementioning
confidence: 99%
“…Nine studies were found relating to the police custody suite setting ( 23 – 31 ). Six studies were classified as low risk ( 23 – 25 , 30 , 31 ), two as medium risk ( 28 , 29 ) and one as high risk ( 26 ). Eight were conducted in England and one in Sweden ( 25 ) and included 12,897 participants (range 12–4,739) and the majority of participants were male ( Table 1 ).…”
Section: Results—prevelance—adultsmentioning
confidence: 99%
“…In total, 13 studies were included ( Tables 2 , 3 ). Seven studies were from the UK ( 26 , 28 30 , 32 , 34 , 37 ) and six from the USA ( 42 , 56 , 58 61 ).…”
Section: Results—interventionsmentioning
confidence: 99%
“…While the ability of healthcare providers to prevent or modify such behaviors has not been proven, it might be possible to direct medical effort to the prevention of alcohol and drug-associated problems and, by that, prevent injury, violence, and medical complications of drug abuse 86 . Early detection and interventions that have proven effective for addictions include brief counselling, referral to ambulatory and inpatient treatment programs, community organizations, and appropriate medication use for substance use withdrawal 87 89 . Likewise, screening for exposure to relationship violence (i.e., adult and child abuse and sexual assault) and developing long-term plans and referrals to appropriate community and governmental agencies may prevent assault related TBIs 90 .…”
Section: Discussionmentioning
confidence: 99%